FACTORS THAT DETERMINE BRAND TRUST IN THE INTEREST OF BUYING MULTI LEVEL MARKETING (MLM) PRODUCTS IN THE CITY OF RUTENG MANGGARAI - Maria Epelita Masriani; I Gede Sanica (STIE Mandala Jember, 2022)
In the business world, achieving the goals that have been planned depends very much on the factors that influence it. One of them is the factor of brand trust or brand trust. The concept of trust comes from the analysis of personal relationships in the field of social psychology. Social psychology discusses the influence of humans on others in terms of changing behavior, attitudes, communication patterns, and building trust. According to Hong Youl Ha and Helen Perks (2015) brand trust is a benchmark for customers to rely on the brand's ability to carry out the functions it plays. In this situation where the individual cannot objectively evaluate the quality of the product in advance, brand trust plays an important role in reducing uncertainty in purchasing.This study focuses on the millennial generation of brand trust in buying interest in HWI products. Using a qualitative approach, with descriptive analysis. This study collected data through interviews, observations and documentation. The results of this study were that brand trust had an effect on buying interest in HWI products in the city of Ruteng Manggarai. Keywords: Brand Trust, Buying Interest, MLM Product